2020
DOI: 10.3389/fmicb.2020.01361
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Species for Synthetic Community Design: Network Analyses of Functional Core Microbiomes

Abstract: Constructing biological communities is a major challenge in both basic and applied sciences. Although model synthetic communities with a few species have been constructed, designing systems consisting of tens or hundreds of species remains one of the most difficult goals in ecology and microbiology. By utilizing high-throughput sequencing data of interspecific association networks, we here propose a framework for exploring "functional core" species that have great impacts on whole community processes and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 115 publications
0
34
0
Order By: Relevance
“…To date, most studies have used natural periphyton communities ( Bowes et al, 2012 ; Baxter et al, 2013 ) with varying success. Given the importance of hub abundance to microbiome function demonstrated here and in other microbiomes, higher success may be achieved through a synthetic microbiome approach ( Toju et al, 2020 ) utilizing microbial hubs identified in the microbial network analyses to maximize periphyton functionality.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies have used natural periphyton communities ( Bowes et al, 2012 ; Baxter et al, 2013 ) with varying success. Given the importance of hub abundance to microbiome function demonstrated here and in other microbiomes, higher success may be achieved through a synthetic microbiome approach ( Toju et al, 2020 ) utilizing microbial hubs identified in the microbial network analyses to maximize periphyton functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Biological communities, with desirable functions, can be designed by selecting species with selected traits and gradually adding more species and screening pairs forming favourable interactions. Conversely, it has been proposed that systematical exploration of combinations of species/strains could potentially maximise desired ecosystem functionalities 25 . This approach utilises microbial interaction networks (e.g.…”
Section: Practical Considerations For Synthetic Metagenomesmentioning
confidence: 99%
“…In this way, species are selected according to their topological position in the network, community-scale functional capability and community-scale functional balance. Selected functional core microbiomes are expected to organise whole ecosystem processes and functions 25 . These synthetic microbial communities can then be utilised to unveil the metabolic and molecular mechanisms involved in inter-species interactions.…”
Section: Practical Considerations For Synthetic Metagenomesmentioning
confidence: 99%
“…In this case, transplantation of the normal microbiota can effectively restore the infected microbiota back to normal (Bakken et al 2011). However, simply implanting a desirable microbiota is not a universal method for its establishment (Rilling et al 2015, Castledine et al 2020), and a more systematic methodology is required (Mueller and Sachs 2015, Sbahi and Di Palma 2016, Toju et al 2020). Thus, there is growing momentum for developing a methodology to account for compositional stability in multispecies communities that can provide a basis for predicting, preventing and controlling large-scale shifts in community compositions.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, transplantation of the normal microbiota can effectively restore the infected microbiota back to normal (Bakken et al 2011). However, simply implanting a desirable microbiota is not a universal method for its establishment (Rilling et al 2015, Castledine et al 2020, and a more systematic methodology is required (Mueller and Sachs 2015, Sbahi and Di Palma 2016, Toju et al 2020.…”
Section: Introductionmentioning
confidence: 99%